Experimental results of water additives in diesel engine combustion chamber - A. V. Bizhaev; S. N. Devyanin (Сельскохозяйственные машины и технологии)
An agricultural sector has an actual problem. It means toxicity of diesel engines, and also their high heat density. The main toxic components such as nitrogen oxides and firm particles are typical for diesel engines. The water additive in fuel reduces heat density and toxicity of engines. At water supply in the combustion chamber there is a cooling of the charge coming to the cylinder. Indicators of engine operation depend on a way of water supply in the combustion chamber. The authors chose for researches two widespread rational ways of water supply in the cylinder: with air and in the form of a water fuel emulsion. A technique of an experimental study consists in comparison of the chosen ways on ecological safety of an internal-combustion engine, its temperature conditions and registration of a limit amount of water before violation of normal operation of the diesel. The authors analysed characteristics of the diesel engine on toxicity of exhaust gases, engine efficiency and temperature condition depending on a way of water supply in cylinders. They carried out tests on load characteristics with a nominal frequency of rotation of a cranked shaft of the diesel that corresponds to power at agricultural operations on a tractor or a harvester. Water supply of 70 percent with air reduces temperature of a piston crown fire surface by 27 percent at average values of the power of 11-13 kW. But at low and maximum loadings this decrease makes about 20 percent. At water supply with a water fuel emulsion this effect is less and on low loadings makes about 5 percent, and at the power of 12-14 kW it reaches 20 percent.